PENGARUH SUHU PIROLISIS TERHADAP KADAR FIXED CARBON DARI KARBON AKTIF KULIT BATANG SAGU - Muhammad Nur Alam (Universitas Cokroaminoto Palopo, 2022)
The purpose of this study was to determine the effect of pyrolysis temperature and chemical activation with phosphoric acid on the fixed carbon content of activated carbon and determine the pyrolysis temperature in the manufacture of activated carbon from sago bark in accordance with SNI.6-3730-1995 standards. Sago plants in Luwu Regency, South Sulawesi Province are plants that contain a lot of starch and lignin-cellulose which have the potential to be used as activated carbon. This research was initiated by smoothing the bark of sago stems with a crusher and then pyrolyzed at temperatures of 4000C, 5000C, 6000C and 7000C and then activated with 10% H3PO4. The results of this study obtained Fixed carbon successively 68.64 %; 70.86%; 76.88%; and 80.51% at various pyrolysis temperatures. Data that meets the standard of SNI No. 06-3730-1995 is at a pyrolysis temperature of 7000C, namely the fixed carbon content of 80.51. These results indicate that activated carbon from sago bark can be recommended as activated carbon that can be applied as an adsorbent in various fields.